Enhancing Students’ Writing Skills via Whatssapp Group at SD Negeri Gelam 1 Candi Sidoarjo - Tri Andayani; Sulistyaningsih Sulistyaningsih (International Journal of English and Applied Linguistics (IJEAL), 2024)
In contemporary human life, along with the development of educational technology, it has also developed. The use of technology in education can influence English teaching and learning methods, in particular writing, which has evolved, namely using online writing forums. Online writing forums provide many benefits for researchers or students such as the WhatsApp Group platform as a means of communication. This study aims to improve the ability of students of SD Negeri Gelam 1Candi, Sidoarjo in English lessons, especially writing. Because the students' grades have not been able to reach the KKM number determined by the teacher, this study is a classroom action research conducted on 26 students in 3 cycles. During 3 cycles, students are given topics in English and invited to submit written opinions and refute or respond to the opinions of their classmates. Based on the results of the study, students' writing ability scores using WhatsApp Group, in Pre-cycle got a score of ? 75 (19%), Cycle 1 got a score of ? 75 (75.07%), and Cycle 2 got a score of ? 75 (100%). Scores reflecting students' writing ability, as assessed through WhatsApp Group, showed improvement in 21 students, or 80.76% when comparing the pre-cycle period with cycle 2. It is proven that the use of WhatsApp Group can improve students' learning ability. Writing skills improved after using WhatsApp Group as a strategy for writing text. The research reflects positive perceptions among students regarding the use of WhatsApp Groups in improving their writing skills, with significant benefits seen in creativity, expression, and overall writing quality. And students are declared graduates because they can obtain and exceed the specified KKM score.